The Design Concept of an Electric Amphibious Bus as an Alternative Mass Transportation on Rivers and Roads to Overcome Congestion in the Jabodetabek - Ardan Nagra Coutsar; Sovian Aritonang; Sjafrie Sjamsoeddin; Ade Bagdja (Department of Naval Architecture - Diponegoro University, 2023)
Due to the high growth of vehicles in Jakarta that is not balanced by the growth of roads, the congestion level in Jakarta has been increasing yearly. To overcome the congestion, innovation is needed to utilize the rivers as a means of public transportation. The design uses the spiral design method with a parent design approach. The calculations carried out include the calculation of resistance, calculation of motor power requirements, calculation of longitudinal strength, calculation of construction, calculation of weight, hydrostatic calculation, stability calculation and seakeeping calculation on water vehicles. As for road vehicles, the calculations carried out include wind drag calculation, rolling resistance calculation, incline force calculation, total resistance calculation, torque calculation and electric power calculation. As a result of the calculations and iterations carried out, the technical specifications of the amphibious bus are obtained, including a length of 12.0 m, breadth of 3.0 m, depth of 3.0 and draught of 0.8 m. This bus is equipped with three movers of waterjet propulsion connected to electric motors with a power of 710 kW each. This bus can carry 51 people with one driver. This bus has good stability when in the water under empty and full load conditions with a level of comfort that meets ISO standards. In addition, this bus can operate up to 359 km for water distances and 501 km for land distances at 40 km/h for water and 60 km/h for land for one battery charging. This bus can also run with a maximum angle of up to 30 degrees.